Protected areas enter a new era of uncertain challenges: extinction of a non‐exigent falcon in Doñana National Park. (20th October 2021) - Sergio, F.; Blas, J.; Tanferna, A.; Hiraldo, F.
Abstract: Protected areas are supposed to maintain viable populations of plant and animal taxa and shield them from anthropogenic threats, but this role is increasingly under scrutiny. Here, we document the alarming extinction of a small falcon, the Eurasian hobby Falco subbuteo, in Doñana National Park, an iconic protected area renowned for its rich predator community. Hobbies were originally abundant at 50–60 pairs and acted as unique specialist hunters of swifts and dragonflies. This diet implies a unique niche within the raptor assemblage and frequent ranging over agricultural areas surrounding the park. The high density of other raptors likely constrained habitat availability. Predation was the main cause of breeding failure, and hatching and breeding success were always low, especially in drought years, and declined progressively through time. The extinction occurred rapidly after 2000 with several clues suggesting the synergistic contribution of prey depletion, farmland intensification, chemical contamination, predation and climate warming. Lack of detailed monitoring prevented a clear assessment of the relative role of these factors, but most of them seemed traceable to farming practices and climate change, i.e. large‐scale drivers generated outside the Park. The documented extinction is alarming because this species is not particularly exigent, it may imply widespread declines of other species, and because this loss adds to the imminent local extinction of another raptor with profoundly different requirements, suggesting mounting, broad‐level pressures affecting the whole ecosystem. This unforseen, rapid extinction in a Park that dedicates much effort to raptor management offers broad‐scale reflections. Climate change and growing anthropogenic pressures will make unexpected species losses increasingly common in protected areas, which will face growing difficulties in identifying decline‐drivers and in performing their protective task. Increased knowledge, quality monitoring and rapid management action will be needed for protected areas to deliver their role, but this will require increased funding. Abstract : While protected areas are supposed to maintain viable populations of plant and animal taxa and shield them from anthropogenic threats, this role is increasingly under scrutiny, and here we document the alarming extinction of a small falcon in Doñana National Park. The documented extinction is alarming because this species is not particularly exigent, it may imply widespread declines of other species, and because this loss adds to the imminent local extinction of another raptor with profoundly different requirements, suggesting mounting, broad‐level pressures affecting the whole ecosystem. This unforeseen, rapid extinction in a Park that dedicates much effort to monitoring and management offers broad‐scale reflections: climate change and growing anthropogenic pressures will make unexpected species losses increasingly common in protected areas, which will face growing difficulties in identifying decline‐drivers and in performing their protective task.